Mewujudkan Ekonomi Digital yang Inklusif: Pelatihan Keterampilan Digital untuk Mendorong Kemandirian Ekonomi Kelompok Penyandang Disabilitas di Kabupaten Bintan: Realizing an Inclusive Digital Economy: Digital Skills Training to Encourage the Economic Independence of People with Disabilities in Bintan Regency - Pratiwi, Risdy Absari Indah; Nuraini, Lia; Chahyadi, Ferdi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
People with disabilities often face barriers to accessing economic opportunities and formal employment due to physical limitations and a lack of digital skills. This community service activity aims to empower groups of people with disabilities in Bintan Regency through digital skills training, such as graphic design, digital marketing, and social media management. This activity involved 10 participants from the Indonesian Association of Persons with Disabilities (PPDI) DPC Bintan, held on 26-28 August 2024. This training is expected to improve the participants' ability to utilize digital technology to create business opportunities and increase their economic independence. Based on the evaluation, participants demonstrated significant skill improvement and readiness to apply their new skills in independent business.